Middle Knowledge and the Grounding Objection: A Modal Realist Solution - Sijuwade, Joshua R. (European journal for philosophy of religion, 2022)
This article aims to provide a defense of the coherence of the doctrine of middle knowledge against the Grounding Objection. A solution to the Grounding Objection is provided by utilising the metaphysical thesis of Modal Realism proposed by David K. Lewis (as further developed by Kris McDaniel and Philip Bricker). Utilising this metaphysical thesis will enable the Counterfactuals of Creaturely Freedom, that are part of God's middle knowledge, to have pre-volitional truthmakers, and thus, ultimately, we will have a means to finally deal with this problematic issue that has often been raised against this doctrine.